A rare lesion of the wanderer’s nerve with an unusual postoperative complication: vagal nerve schwanomma - B., Jagnnatha; Dasappa, Pandu; Hanumaiah, Suhasini; Sheeja, Arunima (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Vagal nerve schwannomas are rare parapharyngeal tumours which was first described by Figi in 1933. Hoarseness is the most common symptom. Occasionally, a paroxysmal cough may be produced on palpating the mass. This is a clinical sign, unique to vagal schwannoma. Presence of this sign, along with a mass located on the medial border of the sternocleidomastoid muscle, should make clinicians suspicious of vagal nerve sheath tumours. However, in our case, the patient presented to us with a swelling in the neck and no other symptoms. MRI in the pre-operative work-up is helpful in defining diagnosis and in evaluating the extent and the relationship. A careful intracapsular enucleation with nerve-sparing technique remains the treatment of choice in order to avoid nerve injury which can lead to vocal cord paralysis. Horner’s syndrome following cervical surgeries is a rare phenomenon. Its occurrence following excision of a vagal schwannoma can occur due to direct injury to cervical sympathetic chain during excision or indirect injury due to traction on the sympathetic chain. Here is a case report of a patient diagnosed with left vagal scwanomma who developed horner’s syndrome post operatively.